2021
DOI: 10.2147/cmar.s316437
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Prognostic Nutrition Index as a Prognostic Indicator of Survival in Elderly Patients Undergoing Gastric Cancer Surgery

Abstract: Purpose Gastric cancer is a common tumor type associated with nutritional and immune status. The aim of the current study was to investigate the prognostic value of a preoperative prognostic nutritional index (PNI), composed of nutritional factors and immune factors in elderly patients undergoing gastric cancer surgery. Patients and Methods A total of 454 patients undergoing gastric cancer surgery were divided into two groups based on preoperative PNI scores: ≤45.1 ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The preoperative PNI is an independent prognostic factor for disease-free along with age and TNM stage in GC patients after surgery [21]. A recent study found that preoperative PNI is a sensitive and specific prognostic predictor among elderly patients undergoing gastric cancer surgery [22]. The result in our study showed that low PNI is an independent risk factor associated with prolonged LOS, suggesting that PNI is a predictor for both short-term and long-term outcomes for elderly patients.…”
Section: Discussionsupporting
confidence: 58%
“…The preoperative PNI is an independent prognostic factor for disease-free along with age and TNM stage in GC patients after surgery [21]. A recent study found that preoperative PNI is a sensitive and specific prognostic predictor among elderly patients undergoing gastric cancer surgery [22]. The result in our study showed that low PNI is an independent risk factor associated with prolonged LOS, suggesting that PNI is a predictor for both short-term and long-term outcomes for elderly patients.…”
Section: Discussionsupporting
confidence: 58%
“…Currently, screening for these markers requires additional cost to the patient and redundant targeted testing. As a highly accessible and reproducible biomarker, the association of PNI nutritional status indicators and SII inflammatory indicators with prognosis in patients with various tumors, including gastric cancer, has received increasing attention ( 39 41 ). However, few studies have focused on the relationship between SII and PNI on sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…A significant proportion of HF patients have malnutrition due to chronic energy loss, inflammation, hemodilution, concomitant liver/kidney diseases, infection, and inadequate self-care (Ajayi et al, 1999;Carr et al, 1989;Pasini et al, 2003). It is known that malnutrition predisposes to recurrent infections as well as causes chronic inflammation (Zhang et al, 2021a(Zhang et al, , 2021b.…”
Section: Introductionmentioning
confidence: 99%
“…The prognostic nutritional index (PNI) (Buzby et al, 1980), first proposed by Buzby et al in 1980, is calculated mainly by counting serum albumin and peripheral blood lymphocytes, and can comprehensively reflect the nutritional status and immune status of patients (Kwag et al, 2014; Schwegler et al, 2010). It has been shown in some studies that malnutrition scoring systems may be associated with prognosis in various malignancies, chronic inflammatory diseases, and chronic cardiovascular diseases (Ren et al, 2021; Wu et al, 2021; Zhang et al, 2021a, 2021b).…”
Section: Introductionmentioning
confidence: 99%